Software testing concepts & tools - Pusuluri, Nageswara Rao (Dreamtech Press, 2007)
Software Testing Concepts and Tools provide experience based practices and key concepts that can be used by any organization to implement a successful and efficient testing process. This book provides experience based practices and key concepts that can be used by an organization to implement a successful and efficient testing process. The prime aim of this book is to provide a distinct collection of technologies and discussions that are directly applicable in software development organizations to improve the quality and avoid major mistakes and human errors. The book covers the key concepts in this book range from process and management based topics, including Software Requirements and Design Documents, Software Project Planning, Testing Measurements/ Metrics, Change and Configuration Management, SQA Review Plan, including, Testing Team Formation, Documentation in IEEE 829 formats, Unit and Integration Testing embedded into Development Process, Functional and System Testability